A microchip device to enhance free flow electrophoresis using controllable pinched sample injections. Issue 16 (19th March 2019) - Zhou, Wanjun; Xia, Ling; Xiao, Xiaohua; Li, Gongke; Pu, Qiaosheng
Abstract: Micro free flow electrophoresis (µFFE) is a valuable technique capable of high throughput rapid microscale electrophoretic separation along with mild operating conditions. However, the stream flow separation nature of free flow electrophoresis affects its separation performance with additional stream broadening due to sample stream deflection. To reduce stream broadening and enhance separation performance of µFFE, we presented a simple microfluidic device that enables injection bandwidth control. A pinched injection was formed in the reported µFFE system using operating buffer at sample flow rate ratio ( r ) setting. Initial bandwidth at the entrance of separation chamber can be shrunk from 800 to 30 µm when r increased from 1 to 256. Stream broadening at the exit of separation chamber can be reduced by about 96% when r increased from 4 to 128, according to both theoretical and experimental results. Moreover, the separation resolution for a dye mixture was enhanced by a factor of 4 when r increased from 16 to 128, which corresponded to an 80% reduction in sample initial bandwidth. Furthermore, a similar enhancement on amino acids separation was obtained by using injection control in the reported µFFE device and readily integrated into online/offline sample preparation and/or downstream analysis procedures.